Qualidade de ovos de codornas japonesas submetidos a diferentes condições de armazenamento - Figueiredo, Anderson Neves (2013)
The aim of this study was to evaluate the quality of quail eggs stored under refrigeration, subjected to different types of packaging and storage periods. Used a total of 360 eggs of Japanese quail. The experimental design was completely randomized in a factorial design 3x10 (3 types of packages x 10 storage periods), in other words, eggs were stored under refrigeration, using cartons, Styrofoam and plastic in different storage periods (0, 5, 10, 15, 20, 25, 30, 35, 40, and 45 days), with 12 repetitions. The variables analyzed for egg quality were: weight loss in percentage, Haugh unit, albumen pH, specific gravity, pH of yolk and albumen height. The statistical analyzes of the characteristics evaluated were performed in accordance with the program SAEG (System for Statistical Analysis), developed by the Federal University of Viçosa - UFV (2000), established by the quadratic regression model and the means were compared by Tukey test a 5% probability. Observed for most of the variables were significant differences (P<0.05) in different types of packaging, storage time and interaction between the types of packaging and storage periods, except for the weight loss (%) who presented only significant difference in the different periods of storage. It is concluded that regardless of the type of packing material quail eggs stored up to 45 days after laying, the temperature of 2.7ºC remain in standard of excellent quality for consumption.